Evidence on real exchange rate-inflation causality: an application of Toda-Yamamoto dynamic granger causality test - Umar, Mohammed; Dahalan, Jauhari (Medwell Journals, 2015)
The study provides further evidence of the real exchange rate and inflation causal relationship using Toda and Yamamoto augmented granger causality test in Malaysia, Nigeria, Philippines and South Africa. The critical values used in this study are simulated based on the leverage bootstrap.The results are compared between the granger asymptotic ch-square distribution, the modified WALD test statistics and the leverage bootstrapped distribution critical values. Conflicting findings are obtained which prove the existence of size distortion and nuisance parameter estimates when the former method is applied.The result based on the Toda-Yamamoto and leverage bootstrapped critical values reveal that policy intervention on inflation can stabilize real exchange rate in Malaysia and Nigeria but not vice versa. Moreover, bidirectional causation exists in Philippines and South Africa meaning that any policy intervention formulated on one variable can stabilize the other.The policy implication of this finding is that the policy makers can manipulate the rate of inflation to stabilize real exchange rate fluctuatiom in all countries under study but can only regulate inflation through exchange rate in the case of Phlippines and South Africa